2011
DOI: 10.1111/j.1743-6109.2010.02091.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sexual Functions in Turkish Alcohol-Dependent Males

Abstract: Introduction It was reported that long-term and high amount of alcohol consumption cause sexual dysfunction in men. There is a lack of descriptive studies focusing on the sexual dysfunction of alcohol dependent men in Turkey. Aims This study was conducted to evaluate sexual functions of alcohol dependent men. Methods This descriptive study was performed at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 21 publications
3
20
2
Order By: Relevance
“…Although its effect size was always low, alcohol was the substance that most impaired sexual arousal. Our data, like those of Dişsiz and Oskay [51], partially contradict those of other authors [4,52,53] who argued that alcohol causes transient erectile dysfunction. Although the present study found this area to be impaired, it does not seem to be just a temporary problem, because erectile ability was still affected after a year and, according to the results, did not seem likely to improve just with abstinence.…”
Section: Discussioncontrasting
confidence: 74%
“…Although its effect size was always low, alcohol was the substance that most impaired sexual arousal. Our data, like those of Dişsiz and Oskay [51], partially contradict those of other authors [4,52,53] who argued that alcohol causes transient erectile dysfunction. Although the present study found this area to be impaired, it does not seem to be just a temporary problem, because erectile ability was still affected after a year and, according to the results, did not seem likely to improve just with abstinence.…”
Section: Discussioncontrasting
confidence: 74%
“…Male sexual dysfunction is a considerable health problem that needs to be further evaluated. It is a very common and prevalent chronic problem among people who use drugs worldwide (Chen et al, 2012;Dişsiz & Oskay, 2011). Illicit drugs have harmful effects on male sexual function leading to low self-steam, depression symptoms, and poor health life quality and can be a trigger to drug relapse perceived as beneficial for sexual response (Bang-Ping, 2009;Cioe et al, 2013;Mialon et al, 2012;Okulate et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual disorders ranging from 8% to 95.2% have been reported in men who have chronic alcohol use. [ 8 9 10 11 12 13 14 15 16 ] The common dysfunctions reported were lack of sexual desire,[ 10 11 12 ] premature ejaculation,[ 13 15 ] and erectile dysfunction. [ 14 16 17 ] Some of the predictors of sexual dysfunction noted were advancing age, low educational level, unemployment, early age of onset of alcohol use, greater duration of alcohol dependence, concurrent tobacco use, greater quantity and frequency of drinking, and presence of liver disease.…”
Section: Introductionmentioning
confidence: 99%